One-Pot Fabrication and Characterization of Silver Nanoparticles Using Solanum lycopersicum: An Eco-Friendly and Potent Control Tool against Rose Aphid, Macrosiphum rosae. (11th October 2016) - Bhattacharyya, Atanu; Prasad, Ram; Buhroo, Abdul A.; Duraisamy, Prabha; Yousuf, Insha; Umadevi, M.; Bindhu, M. R.; Govindarajan, Marimuthu; Khanday, Abdul L.
Abstract : The espousal of nanotechnology is a current come-up of the present revolution. As we know that the rose aphid, Macrosiphum rosae (Hemiptera: Aphididae), is a key pest on rose plant in Kashmir Valley, India, it exhibits a worldwide distribution. In the present study, we have synthesized biologically silver nanoparticles (Ag NPs) from Solanum lycopersicum and characterized them by UV-vis spectroscopy, TEM, and X-RD analysis. The experiment was performed by leaf dip method. Insecticidal solutions of different Ag NPs concentrations, namely, 200, 300, 400, and 500 ppm, were tested on M. rosae . For assessment purposes, leaves were treated with distilled water (used as control). Aphid mortality data revealed that the Ag NPs were effective at 500 ppm concentration. As the concentration and day's treatment increased, the aphid mortality rate also increased. There were statistically significant differences in M. rosae mortality between concentrations by LSD at 5%. In wrapping up, the use of Ag NPs in pest control processes will be the most novel eco-friendly approach in the Kashmir Valley, India, in future.